STUDI TENTANG INDUSTRI MAKANAN TRADISIONAL PINYARAM DI KORONG TITIAN PANJANG NAGARI KAYU TANAM KECAMATAN 2X11 KAYU TANAM KABUPATEN PADANG PARIAMAN - Gusniati, Rina (Pendidikan Geografi, 2013)
The research aims to determine how is the situation of capital industry traditional food pinyaram, wroker, marketing, income and constraints that find by the traditional food industry pinyaram in village of Titian Panjang, Kayu Tanam village 2x11 Kayu Tanam subdistrict. Research method is used descriptive. Population and sample this research is the traditional food industry pinyaram in village of Titian Panjang Kayu Tanam village 2x11 Kayu Tanam Subdistrict Padang Pariaman Regency, and as the sample in area village of Titian Panjang with respondents 12 people with a total sampling. Based on data analysis, so results of research findings that: (1) The entrepreneurs of traditional food industry pinyaram get financial capital of effort from individual financial capital with the percentage (91,67%), (2) The worker used to produce tradisional food pinyaram are free workers with the percentage (50%), (3) In distributing results of traditional food pinyaram are entrepreneurs themselves with the percentage (75%), (4) The income which get sufficient to daily needs with the percentage (83,33%), (5) The constraints faced by the traditional food industry pinyaram is difficult to get employment fixed by percentage (66,67%).